Suppression of cell migration is promoted by miR-944 through targeting of SIAH1 and PTP4A1 in breast cancer cells - Flores Pérez, Ali; Marchat, Laurence A.; Rodríguez Cuevas, Sergio; Piña Bautista, Verónica; Fuentes Mera, Lizeth; Romero Zamora, Diana; Maciel Domínguez, Anabel; De la Cruz, Olga Hernández; Fonseca Sánchez, Miguel; Ruíz García, Erika; Astudillo de la Vega, Horacio; López Camarillo, César (2016)
Background: Aberrant expression of microRNAs has been associated with migration of tumor cells. In this study, we aimed to investigate the biological significance of miR-944 whose function is unknown in breast cancer. Methods: MiR-944 expression in breast cancer cells and tumors was evaluated by Taqman qRT-PCR assays. Transcriptional profiling of MDA-MB-231 cells expressing miR-944 was performed using DNA microarrays. Cell viability, migration and invasion were assessed by MTT, scratch/wound-healing and transwell chamber assays, respectively. The luciferase reporter assay was used to evaluate targeting of SIAH1, PTP4A1 and PRKCA genes by miR-944. SIAH1 protein levels were measured by Western blot. Silencing of SIAH1 gene was performed by RNA interference using shRNAs. Results: Our data showed that miR-944 expression was severely repressed in clinical specimens and breast cancer cell lines. Suppression of miR-944 levels was independent of hormonal status and metastatic potential of breast cancer cells. Gain-of-function analysis indicated that miR-944 altered the actin cytoskeleton dynamics and impaired cell migration and invasion. Genome-wide transcriptional profiling of MDA-MB-231 cells that ectopically express miR-944 showed that 15 genes involved in migration were significantly repressed. Notably, luciferase reporter assays confirmed the ability of miR-944 to bind the 3´UTR of SIAH1 and PTP4A1 genes, but not PRKCA gene. Congruently, an inverse correlation between miR-944 and SIAH1 protein expression was found in breast cancer cells. Moreover, SIAH1 was upregulated in 75 % of miR-944-deficient breast tumors. Finally, SIAH1 gene silencing by RNA interference significantly impaired cell migration of breast cancer cells. Conclusions: Our results pointed out that miR-944 is a novel upstream negative regulator of SIAH1 and PTP4A1 genes and provided for the first time evidence for its functional role in migration and invasion of breast cancer cells. They also suggest that miR-944 restoration may represent a potential strategy for breast cancer therapy.